Еffect of laser treatment on the structure and properties of piston rings - Selezniov, S.; Селезньов, С. В. (Харківський національний автомобільно-дорожній універститет, 2024)
The study is devoted to the urgent problem of increasing the durability of armored vehicle engines by applying advanced laser processing technology. The object of study is piston rings that are subjected to laser processing in order to form special structures on the surface that provide increased wear resistance. The obtained results made it possible to establish the regularities of formation of the structure and properties of the surface layers of piston rings depending on the parameters of laser processing. The optimal modes of laser processing were determined, which ensure the maximum increase in wear resistance and durability of piston rings.The results of the study can be used to develop new technologies to improve the reliability and durability of armored vehicle engines.
Вплив лазерноі обробки на структуру та властивості поршневих кілець
Keywords: laser processing; piston rings; wear resistance; durability.; лазерна обробка; поршневі кільця; зносостійкість; довговічність.; 621.785